Sejarah Perkembangan Konsep Qaṭ’i-Zannī: Perdebatan Ulama Tentang Anggapan Kepastiaan dan Ketidakpastian Dalil Syari’at - Muhyar Fannani (Al-Jami'ah: Journal of Islamic Studies, 2001)
The concept of certainty (qat’i) and uncertainty (ẓannī) of shari'ah argumentation (dalil) in the Islamic Legal Theory has played a big role to help a jurist in taking ijtihad or not, related to the shari'ah argumentation. This paper discusses this concept from historical perspective. Based on the historical proof, apparently, the concept of certainly and uncertainty, for a long time was understood based on the textualism principle and not on the substantial idea.  As a consequence, qaṭ'i was Qur’anic of Hadith texts that have one meaning although that meaning was not a substantial and universal one,  such as inheritance and robbing verses. On the contrary, the text that has substantial and universal meaning such as the verses that talk about egalitarianism, justice, equality before the law, tolerance, etc, were not considered as qat'i. Finally, Islamic law became rigid and stiff because the local and temporal meaning was forced to be universal one.  The historical journey of this concept indicated that the Origen of this concept emerged since the big ṣahābi era. Then, this concept was sparked officially by ash-Shāfi'ii (w.204H/820M), although he didn't have final term for it. This concept, then, was improved by muslim  scholars after ash-Shāfi'i and became mature concept on the hand to Imam Haramain (w. 478H/1085M). Qaṭl-zānni as a technical term was popularized by the later uslul scholars scah as Abd.'Aziz al-Bukhari ( w.730/7330) and Kamāl b . Humam  (w. 861/1475).  In the modem era, the demand for reconception for the old qaṭ'i-zānni concept urged to be done because of the new challenge for the Islamic law.  The most relevant of the reconception was the reconception that can accommodate precisely the demand of law flexibility in the one hand and law firmness in the other hand. Such reconception can be achieved, if the qaṭ'i-zānni concept was not understood based on textualism anymore, but refers to substantial and universal idea. Thus, qaṭ'i is the verses that contain the universal meaning, and zānni is the verses that contain local and temporal meaning